MORPHOLOGICAL FEATURES OF THE SYNOVIAL MEMBRANE IN EXPERIMENTAL DIABETES MELLITUS - Primova Gulra’no Abdumannapovna; Bo‘riyeva Maftuna Shuxrat qizi (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
This study investigates the morphological changes in the synovial membrane induced by experimental diabetes mellitus using a streptozotocin (STZ)-induced diabetic rat model. Over an 8-week observation period, detailed histological and ultrastructural analyses revealed key alterations, including basement membrane thickening by 2-3 fold, endothelial cell swelling, pericyte degeneration, reduced vascular density by 15-20%, and increased collagen deposition in diabetic animals compared to controls. These pathological modifications were closely associated with elevated markers of oxidative stress, such as nitrotyrosine, and inflammatory cell infiltration, suggesting a progressive microangiopathic and fibrotic process. The findings underscore hyperglycemia's pivotal role in driving structural remodeling of the synovial membrane, which may contribute to synovial dysfunction and related musculoskeletal complications in diabetes. This research extends prior knowledge by integrating temporal dynamics and mechanistic insights, highlighting potential targets for therapeutic intervention.